The Constitutional Court of The Russian Federation as a subject of constitutional responsibility - N. A. Bobrova (Правоприменение, 2021)
The subject of the article is justification of the main elements of the constitutional responsibility of the Russian Constitutional Court in the context of constitutional reform.The purpose of the article is confirmation or refutation of the hypothesis that the Constitutional Court must be subject to constitutional responsibility.The methodology. The author uses methods of complex analysis of legislation, synthesis, as well as formal-logical and formal-legal methods.The main results, scope of application. Russia as a democratic state excludes the existence of legally irresponsible subjects of state power. It concerns the Constitutional Court of the Russian Federation. Legal irresponsibility characterizes only the absolute monarchy. The article comprehensively examines the problem of responsibility of the Constitutional Court of the Russian Federation, the reasons for the poor development of this institution in legislation and academic literature are also considered. The reasons for the Constitutional Court's dependence on the President of the Russian Federation as a "guarantor of the Constitution of the Russian Federation" have been systemized. The author considers duumvirate of guarantors of constitutional legitimacy as a nonsense. The reasons for the Constitutional Court's peculiar use of the law of the legislative initiative are considered. This initiative was used only in the direction of increasing the term of the powers of judges of the Constitutional Court from 65 up to 70 years. The life-long status of the President of the Court is seen as a violation of the principle of equality of judges, which is the most important guarantee of the independence of the Constitutional Court. Constitutional reform-2020 completed the process of dependence of the Constitutional Court on the President of the Russian Federation and the "second government" - the Administration of the Russian President. Some constitutional and legal torts of the Constitutional Court of the Russia are considered also. The author comes to the conclusion that judges of the constitutional court have a special responsibility - political, moral and historical. The main questions are need to be resolved: who has the right to state the torts of the constitutional court and what are the consequences of this statement?